Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1001/jamapediatrics.2020.3694
|View full text |Cite
|
Sign up to set email alerts
|

Muslim Young Adult Mental Health and the 2016 US Presidential Election

Abstract: Role of the Funder/Sponsor: The funder had no role in the design and conduct of the study; collection, management, analysis, and interpretation of the data; preparation, review, or approval of the manuscript; and decision to submit the manuscript for publication. Disclaimer:The opinions, findings, and conclusions herein are those of the authors and not necessarily represent those of the Regents of the University of California or any of its programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…For example, the 2016 presidential election was associated with a rise in anti-Muslim rhetoric, policy, and hate crimes (Musu et al, 2019). In HMS data, we found that the election was associated with a significant rise in the proportion of Muslim students experiencing mental health symptoms in the 14 months postelection compared with the 14 months prior (Abelson et al, 2020). More recently, racism and acts of violence against Asian American/Pacific Islanders (AAPI) have increased.…”
Section: Public Policy-level Factorsmentioning
confidence: 95%
“…For example, the 2016 presidential election was associated with a rise in anti-Muslim rhetoric, policy, and hate crimes (Musu et al, 2019). In HMS data, we found that the election was associated with a significant rise in the proportion of Muslim students experiencing mental health symptoms in the 14 months postelection compared with the 14 months prior (Abelson et al, 2020). More recently, racism and acts of violence against Asian American/Pacific Islanders (AAPI) have increased.…”
Section: Public Policy-level Factorsmentioning
confidence: 95%
“…Overall, research on the impact of presidential elections on health has consistently found that elections matter to peoples’ health. Given the unprecedented nature of the 2016 election, it should not come as a surprise that a flurry of studies have emerged on the role of the 2016 presidential election and health (Hoyt, et al, 2018; Gonzalez et al 2018; Morey et al 2021; Krueger, Westmoreland, Choi, Harper, Lightfoot, Hammack, and Meyer 2021; Abelson et al 2020; Roche and Jacobson 2019; DeJonckheere, Fisher, and Chang 2018; Yan, Hsia, Yeung, and Sloan 2021; Neupert, Bellingtier, and Smith 2021). Across many different research designs, scholars have consistently found that the 2016 election impacted health in important ways in the United States.…”
Section: Previous Research and Expectationsmentioning
confidence: 99%
“…This study makes several contributions to the literature. First, while previous research has examined the 2008 (Stanton et al 2010; Brown et al, 2021), 2012 (Ben-Ezra, et al, 2013), and 2016 (Hoyt, Zeiders, Chakua, Toomey, and Nair 2018; Gonzalez et al 2018; Morey et al 2021; Krueger, Westmoreland, Choi, Harper, Lightfoot, Hammack, and Meyer 2021; Abelson et al 2020; Roche and Jacobson 2019; DeJonckheere, Fisher, and Chang 2018; Yan, Hsia, Yeung, and Sloan 2021; Neupert, Bellingtier, and Smith 2021) presidential elections, little research has examined the impact of the 2020 election on the health of Americans. This lacuna is especially important given how emotionally-charged and contentious the 2020 presidential election and its aftermath were (Weinschenk, van der Linden, and Panagopoulos 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The 2016 election brought about broad shifts in attitudes and policies related specifically to immigration and more broadly toward people of other national and religious backgrounds, including Muslims. Abelson et al documented an increase in clinically significant mental health symptoms after the election for Muslim college students relative to non-Muslim students.…”
mentioning
confidence: 99%